Level of Understanding of The Health Protocol Slaughtering Qurban Animal During COVID 19 Pandemic in West Kotawaringin District - Ayutha Wijinindyah; Ida Ketut Mudhita (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Slaughtering of animal qurban is a form of worship Muslim. In the current pandemic situation, it is necessary to pay attention to the procedure of slaughtering animal qurban so that their implementation is in accordance with health protocols. This is to make the slaughter of animal qurban in accordance with Islamic law and minimize the pread of covid 19. The data analysis technique in this study was descriptive quantitative with purposive sampling and the analyzed using research instruments. The result show that the public already understands the health protocol for slaughtering animal qurban during pandemic in New Normal. This can been that 92% of the understanding of the slaughter animals is very good. In conclusion, offices generally know health protocol and are able to apply them to sacritificial animal slaughtering activities.